Mindfulness, healthy life skills and life satisfaction in varsity athletes and university students - Arı, Çağrı; Ulun, Cihan; Yarayan, Yunus Emre; Dursun, Mücahit; Mutlu Bozkurt, Tuğba; Üstün, Ümit Doğan (Progress in Nutrition, 2020)
Study Objectives: The present study aimed to investigate the differences in the perception of mindfulness, healthy life skills, and life satisfaction in varsity athletes and university students. Analyzing the correlations between the variables was another aim. Materials and Method: The study was designed as a crosssectional quantitative study, and the study sample consisted of 379 university students from Gazi University. In the study, to collect data Mindful Attention Awareness Scale (MAAS), Healthy Life Skills for University Students Scale, and Satisfaction with Life Scale were used together. In analyzes of the data, independent samples t-test, Partial correlation, and Simple Linear Regression analyzes were used. Results: Results showed that varsity athletes reported significantly higher scores in the importance given to health sub-dimension and life satisfaction regarding group comparisons. On the other hand, there were no significant differences in mindfulness, healthy nutrition, health literacy, and health priority sub-dimensions. Regarding correlations, mindfulness, healthy life skills, and life satisfaction were correlated, and mindfulness significantly predicted healthy life skills and life satisfaction more for non-athlete students. Conclusion: This study showed that varsity athletes attach more importance to health and have higher life satisfaction than non-athletes. However, further research is still recommended.